Optimalisasi Patroli Satuan Sabhara Dalam Mencegah Tindak Pidana Pencurian Dengan Kekerasan Di Wilayah Hukum Polres Bogor - Muhammad Dwindra Okta Arivando (Indonesian Journal of Police Studies, 2021)
According to the phenomenon that occurs in society today, the improvements of technologies and pieces of knowledge affect the way society thinks and acts whereas having an impact in a criminal case such as theft. One of the popular theft cases in Indonesia is the case of theft using violence. In Bogor police jurisdiction, According to the recorded data in 2018 there were 29 cases of fraud and in 2019 there were 62 cases of theft using violence. Sabhara aims to implement the arrangements, guard, escort, and patrol (In Bahasa known as Turjawali), Crime Scene, and Society control in order to maintain the public order and security, as well as securing the headquarter to prevent the case of theft using violence in the society optimally. The purpose of this study is to describe the implementation of the Sabhara unit patrol and the factors that influence the Sabhara unit in preventing the case of theft using violence in the Bogor Police jurisdiction. This study uses a qualitative approach as the type of field research. The location of this study located at Bogor Police. The data collection techniques uses interviews, observation, and document studies. The validity of the data in this study uses data triangulation, interviews, observations, and document studies. The results of this study revealed the Sabhara unit is carrying out patrol activities aimed to prevent the intentions and opportunities of the perpetrators to carry out their crimes. In the implementation of patrol activities in order to prevent the case of theft using violence, most of the units had been carried out as the guidelines according to the SOP (Standard Operating Procedure). External factors that influence the implementation of Sabhara members are the method of implementing patrols which are considered to be appropriate also supported by the patrol location and target. Internal factors that influence the implementation are the human resources of Sabhara members themselves, where Sabhara members of Bogor Police are still outnumbered. As well as the infrastructure obtained by members of Sabhara in carrying out activities in the fostered area is still lacking.